¿Quiénes hacen las reformas? : Políticas de formación docente, reformadores y desplazamientos históricos en la transición democrática (1983-1989) - Mendez, Jorgelina; Giovine, Renata (2018)
La presente tesis analiza las reformas de la formación docente puestas en marcha durante el gobierno de la "transición democrática" (1983-1989) indagando las particularidades que asume la elaboración de la política educativa en este contexto histórico. El abordaje recupera tres ejes considerados fundamentales para el análisis de dichos procesos: los argumentos que las sustentan, los ámbitos donde se elaboran y la figura del reformador. Dichos ejes aluden a la relación, siempre presente en los momentos de reforma, entre el campo de la política educativa y el campo intelectual de la educación convirtiendo al reformador en un actor clave en tanto mediador entre ambos espacios. La centralidad que la formación docente adquirió en las políticas de transformación educativa a lo largo del siglo XX vuelve a estas reformas un objeto interesante para observarlas desde estos ejes de análisis. El período que se recorta en esta tesis es importante por varios motivos. En primer lugar, es un momento fructífero para analizar la relación entre los intelectuales y el gobierno, en tanto supuso nuevas formas de vinculación y una confianza renovada en la política y la democracia luego del largo ciclo de inestabilidad que sobrevino con las últimas dictaduras militares. En segundo lugar, se trató de un momento histórico donde la idea de reforma y transformación estuvo incluída en un intento de "modernización democrática" siendo la educación uno de los pilares de la misma. Finalmente, por que en relación a la reforma y, más específicamente, a la formación docente, evidencia desplazamientos y nuevas formas de intervención dando paso a la, cada vez más directa, participación de organismos internacionales y regionales y otras organizaciones en el proceso de elaboración de la política.
This thesis analyzes the teacher formation reforms started during the "democratic transition" government (1983-1989) inquiring into the particularities assumed by the elaboration of the educational policy in this historic context. The approach recovers three axes considered fundamental for the analysis of said processes: the arguments that support them, the areas where they are elaborated and the figure of the reformer. These axes allude to the relationship, always present in times of reformation, between the field of educationpolicy and the intellectual field of education transforming the reformer into a key actor as mediator between both spaces. The centrality that teacher formation acquired in the educative transformation policies throughout the 20th century turns these reforms into an interesting object to be observed from these axes of analysis. The period drawn in this thesis is important for several reasons. Firstly, it is a fruitful moment to analyze the relationship between the intellectuals and the government, which involved new ways of connection and a renewed confidence in politics and democracy after the long instability cycle that came over along with the last military dictatorships. Secondly, it was a historic moment where the idea of reform and transformation was included in an attempt of "democratic modernization", being education one of the pillars of it. Finally, because in relation to the reform and, more specifically, to teacher formation, shows displacements and new forms of intervention giving way to the, increasingly direct, involvement of regional and international organizations and other bodies in the policy making process.This thesis analyzes the teacher formation reforms started during the "democratic transition" government (1983-1989) inquiring into the particularities assumed by the elaboration of the educational policy in this historic context. The approach recovers three axes considered fundamental for the analysis of said processes: the arguments that support them, the areas where they are elaborated and the figure of the reformer. These axes allude to the relationship, always present in times of reformation, between the field of educationpolicy and the intellectual field of education transforming the reformer into a key actor as mediator between both spaces. The centrality that teacher formation acquired in the educative transformation policies throughout the 20th century turns these reforms into an interesting object to be observed from these axes of analysis. The period drawn in this thesis is important for several reasons. Firstly, it is a fruitful moment to analyze the relationship between the intellectuals and the government, which involved new ways of connection and a renewed confidence in politics and democracy after the long instability cycle that came over along with the last military dictatorships. Secondly, it was a historic moment where the idea of reform and transformation was included in an attempt of "democratic modernization", being education one of the pillars of it. Finally, because in relation to the reform and, more specifically, to teacher formation, shows displacements and new forms of intervention giving way to the, increasingly direct, involvement of regional and international organizations and other bodies in the policy making process.
Keywords: 1983-1989; Política educacional; Formación de docentes; Currículo de formación de docentes; Argentina